PERBANDINGAN KINERJA REM ABS DAN REM BIASA TERHADAP JARAK PENGEREMAN DAN WAKTU PADA MOBIL AVANZA - anam1, khoirul; Prasetyo2, Imam; PutraMahadika3, Hanif; Suprapto4, Suprapto4 (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2020)
Transportation is an important thing in everyday life, especially to support activities that are full of mobility. This makes private vehicle users continue to grow. Therefore, it is necessary to improve performance from all aspects such as comfort, security, and stability. The braking system is one of the important aspects in vehicle design which has a major effect on safety and stability. The purpose of this study was to compare the performance of ABS and Non ABS brakes on Avanza cars to compare the braking distance and time. This test was carried out by direct braking practice on a straight road and repeated 2 times at each speed. The test was carried out with variations in speed, namely 40 km/hour, 50 km/hour, 60 km/hour, 70 km/hour, and 80 km/hour. The results of the car braking test with ABS and Non ABS technology for a speed of 40 Km/hour ABS brakes are 1.70 seconds while Non ABS brakes are 1.78 seconds. So the time difference is 0.08 seconds. For a speed of 80 km/h, the ABS brake is 3.31 seconds while the Non ABS brake is 3.39 seconds, so the difference is 0.08 seconds. From these data, it can be concluded that at a speed of 40 km/hour compared to a speed of 80 km/hour, the time difference is the same, namely 0.08 seconds. at each test speed. In addition, the length of braking time required for each speed variation on vehicles with the ABS braking system is shorter than the non-ABS braking system. In addition, it is also found that the deceleration of vehicles with the ABS braking system is better than the Non-ABS braking systemKeywords: ABS, Non ABS, Braking system